2015
DOI: 10.1021/acs.jpca.5b02942
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Particle Size on the Fundamental Vibrations of the [CO32–] Anion in Calcite

Abstract: This study examines the effects of particle sizes between 3-121µm on the fundamental vibrations of the [CO3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…The reason was possibly that with the decrease in the particle size, the spectral contrast of internal modes decreased, the particle behavior was optically thin incoherent volume scatterers, namely the absorbance of FTIR spectra was the higher and the bandwidth was the narrower (Kristova, Rutt, & Hopkinson, 2015). So the particles increased volume scattering, which would cause the increase in powder intensity (Kristova et al, 2015). These results indicated that the chemical functional groups of TAPs were directly related to the corresponding particle size.…”
Section: Ftir Analysis Of Tapsmentioning
confidence: 94%
See 3 more Smart Citations
“…The reason was possibly that with the decrease in the particle size, the spectral contrast of internal modes decreased, the particle behavior was optically thin incoherent volume scatterers, namely the absorbance of FTIR spectra was the higher and the bandwidth was the narrower (Kristova, Rutt, & Hopkinson, 2015). So the particles increased volume scattering, which would cause the increase in powder intensity (Kristova et al, 2015). These results indicated that the chemical functional groups of TAPs were directly related to the corresponding particle size.…”
Section: Ftir Analysis Of Tapsmentioning
confidence: 94%
“…It was observed corresponding to the C-H stretching vibrations CH 2 (1,041 cm −1 ) group in TAPs (Soares et al, 2001). The reason was possibly that with the decrease in the particle size, the spectral contrast of internal modes decreased, the particle behavior was optically thin incoherent volume scatterers, namely the absorbance of FTIR spectra was the higher and the bandwidth was the narrower (Kristova, Rutt, & Hopkinson, 2015). In addition, the intensity of bands from powders generally decreased with decreasing the powder size.…”
Section: Ftir Analysis Of Tapsmentioning
confidence: 97%
See 2 more Smart Citations
“…The shift of wavenumber values of the strong intense CONH at band 1666 cm −1 (Figure 1a), 1697 cm −1 for PAMPS and PAMPS-Na observed (Figure 1b,c), or the S=O asymmetric stretching and symmetric S=O stretching at 1400 and 1043 cm −1 (Figure 1b,c) compared to their reported values in the literature [35] elucidate the decreasing of PAAm, PAMPS, and PAMPS-Na sizes [36]. These shifts refer to the decrease in the wavelength and penetration depth of the IR light intensity [37]. The thermal stabilities of PAAm, PAMPS and PAMPS-Na were investigated from their TGA thermograms represented in Figure 2 a-c.…”
Section: Characterization Of Paam Pamps and Pamps-na Microgelsmentioning
confidence: 53%